Teknik Self-Management: Strategi Mereduksi Gaya Hidup Hedonis Siswa Sekolah Menengah Pertama - Ishlakhatus Sa'idah; Moh. Ziyadul Haq Annajih; Diana Vidya Fakhriyani (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2023)
Changes in people's lifestyles are one of the impacts of globalization. Globalization can influence how young people meet the demands of their lifestyle. A hedonistic lifestyle is defined as one that prioritizes pleasure and material satisfaction. Most people believe that lifestyle is important because it can show self-identity. The aim of this article is to explain how effective self-management techniques are in reducing the hedonic lifestyle of students at SMPN 2 Pamekasan with six research subjects. This research uses a one-group pretest-posttest experimental design. The data collection methods used in this research were the hedonic lifestyle scale, observation, and interviews. The data analysis technique used is the Wilcoxon signed rank test. The results of the research show that self-management techniques are effective in reducing the hedonic lifestyle of class IX students at SMPN 2 Pamekasan. This can be seen from the asymptotes. The sig (2-tailed) value has a value of 0.008, which is smaller than 0.05 (Ha is accepted).